Neoteinic and dwarf weeds: distribution, biology, control - Kurdiukova, O.; Tyshchuk , O. (Quarantine and plant protection, 2021)
Goal. To determine the features of the distribution, occurrence, biology, harmfulness and methods of control of neoteinic and dwarf weeds in the conditions of the Left Bank Steppе. Methods. The studies were carried out during 2017—2020 by route and expeditionary surveys. Weeds were counted 6—12 times. Results. Neoteinic forms and dwarf plants were found in agricultural crops throughout the growing season. The number of weeds prone to neotenia made up 43 species. The duration of the period from germination to seed ripening varied in them within 14—34 days. Plant height was 2.8—12.4 cm. Their average seed productivity did not exceed 19—21 pcs. from the plant. The mass of 1000 seeds was 12—19% higher, and the germination rate was 21—34% higher than in conventional forms. At an average density of plants, up to 3.43—3.84 thousand pieces/m2 of seeds entered the soil. Stubble ploughing and subsequent basic tillage provided 100% control of them. Late autumn application of herbicides to control neoteinic and other annual weeds was impractical. Dwarf plant species in agrophytocenoses were represented by 27 species. The number of their seedlings in winter crops ranged from 11—16 to 237—334 pieces/ m2, for spring and row crops — from 37—53 to 365—489 pieces/m2. The height of the plants was 10.8—17.5 cm, and the seed productivity was from 6 to 609 pcs. With the density of these weeds at the level of 145—160 pcs/m2, they were consumed in crops of winter wheat 18.9 kg/hectare of nitrogen, 31.0 kg/hectare of phosphorus and 27.8 kg/hectare of potassium. Average water consumption was 141 m3/hectare. The loss of wheat grain was 0.48 t/h. In the fields for grain, cereals and row spring crops, high efficiency of control in all forms and types of weeds was achieved in a system of combination of soil cultivation, which included harrowing, seed bed preparation of autumn plows, as well as the use of herbicides. In the crops of winter wheat and barley, the maximum destruction of weeds was achieved from the use of leaf herbicides in autumn 10—12 days before the end of the growing season or at the beginning of the spring growing season. Conclusions. The main attention in the control system of neotenic and dwarf weeds belongs to the summer-autumn technological method by 1—2-fold stubble plowing. Additionally, in sowing of spring crops, they are destroyed in the system of pre-sowing soil cultivation in combination with herbicides, and in winter crops by the use of leaf herbicides in autumn or early spring.